2018
DOI: 10.22365/jpsych.2018.291.64
|View full text |Cite
|
Sign up to set email alerts
|

Schizophrenia and type 2 diabetes mellitus

Abstract: S chizophrenia is associated with increased risk for type 2 diabetes mellitus, resulting in elevated cardiovascular risk and limited life expectancy, translated into a weighted average of 14.5 years of potential life lost and an overall weighted average life expectancy of 64.7 years. The exact prevalence of type 2 diabetes among people with schizophrenia varies across studies and ranges 2-5fold higher than in the general population, whereas the aetiology is complex and multifactorial. Besides common diabetogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
48
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 58 publications
3
48
0
2
Order By: Relevance
“…For example, in Victoria six per cent of all adults have been diagnosed with type 2 diabetes; however, in the population of service users with mental illness in the years 2015-2016, 10.6% of these service users had a diagnosis of type 2 diabetes (Victorian Government, 2017). This finding has also been replicated in other studies, finding type 2 diabetes twice as prevalent in service users with a diagnosis of serious mental illness when compared to the general population (Annamalai, Kosir, & Tek, 2017;Mamakou, Thanopoulou, Gonidakis, Tentolouris, & Kontaxakis, 2018). This internationally important issue was highlighted in another study that found service users with depression suffered nearly three times more chronic medical conditions than those without depression (Druss, Rask, & Katon, 2008).…”
Section: Introductionsupporting
confidence: 59%
“…For example, in Victoria six per cent of all adults have been diagnosed with type 2 diabetes; however, in the population of service users with mental illness in the years 2015-2016, 10.6% of these service users had a diagnosis of type 2 diabetes (Victorian Government, 2017). This finding has also been replicated in other studies, finding type 2 diabetes twice as prevalent in service users with a diagnosis of serious mental illness when compared to the general population (Annamalai, Kosir, & Tek, 2017;Mamakou, Thanopoulou, Gonidakis, Tentolouris, & Kontaxakis, 2018). This internationally important issue was highlighted in another study that found service users with depression suffered nearly three times more chronic medical conditions than those without depression (Druss, Rask, & Katon, 2008).…”
Section: Introductionsupporting
confidence: 59%
“…It is well known that antipsychotics are associated with an increased risk of obesity, metabolic syndrome and diabetes mellitus 53 . Excess mortality and all-cause hospitalizations could be explained by aggravating factors for T2D onset and poor diabetes management present in individuals with schizophrenia, such as excessive sedentary lifestyle, social determinants, adverse effects of antipsychotic drugs or limited access to medical care 53,54 .…”
Section: Discussionmentioning
confidence: 99%
“…We calculated the prevalence of each type of mental health comorbidity in the study population by sex and age group (i.e., [45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64], 65-74, 75-84 and ≥ 85 years). We analysed demographic and clinical information of the study population according to the presence or not of mental health comorbidity by means or frequencies/proportions.…”
Section: Discussionmentioning
confidence: 99%
“…Schizophrenia has long been found to link with increased risk of T2DM, as the prevalence of type 2 diabetes is 2–5-fold higher in patients with schizophrenia when compared with those without DM (Mamakou et al, 2018 ). While this may due to the impact of antipsychotic treatment and also the disease progression, the fact that drug native patients of schizophrenia were still at 1.27–1.63-fold of risk of having T2DM than general population (Cohen and De Hert, 2011 ) may suggested that there is uniquely shared risk factor between the two diseases.…”
Section: Discussionmentioning
confidence: 99%